Bacterioplankton Succession During the Arctic Ocean Spring Bloom - Pedrós-Alió, Carlos; Puente-Sánchez, Fernando; Macías, Luis Alberto; Redondo, Álvaro; Campbell, Karley L.; Royo-Llonch, Marta; Balagué, Vanessa; Sánchez, Pablo; Mundy, Christopher-John; Tamames, Javier (2022)
VIII International Symposium on Marine Sciences, 6-8 July 2022, Las Palmas de Gran Canaria, España Environmental conditions change dramatically from winter to summer in the Arctic Ocean. As the sea ice melts, large amounts of algal polysaccharides are released in the water column while simultaneously the main phytoplankton bloom develops beneath the ice. These changes are reflected in the taxonomic composition of the heterotrophic bacterioplankton within the upper water column. The dominant taxonomic groups in winter are Alpha- and Gammaproteobacteria and Thaumarcheota. In contrast, Bacteroidetes and Gammaproteobacteria are instead dominant during the spring-summer bloom period. Here we present a time series from early March to late July in Dease Strait (Canadian Arctic) where metagenomes and metatranscriptomes from the planktonic bacterial size fraction were obtained over a spring ice algal bloom to investigate the causes of this transition in microbial community composition. Looking at the genes present and expressed, two main traits seemed to allow Bacteroidetes to dominate. First, they had a large collection of polysaccharide degradation genes. In March, on the other hand, glycosyl-hydrolases degraded a variety of compounds including fucoidan, a cell wall polysaccharide of diatoms. During the bloom, on the other hand, glycosyl-hydrolases for laminarin, a storage polysaccharide of diatoms, became extremely abundant. Thus, Bacteroidetes were in the optimal position to take advantage from the diatom polysaccharides and had transporters to incorporate iron siderophore complexes. However, they did not show genes for the synthesis of siderophores (Puente-Sánchez et al. 2022). This task was carried out almost exclusively by Gammaproteobacteria. Clearly, the ability to steal iron from other bacteria and to use algal polysaccharides are two traits favouring the dominance of this phylum in summer Sequencing and data analysis were funded by grant PID2019-110011RB-C33 from the Agencia Estatal de Investigación of the ...